Why do private acquirers pay so little compared to public acquirers?☆ - BARGERON, L; SCHLINGEMANN, F; STULZ, R; ZUTTER, C (Journal of Financial Economics, 2008)
Using the longest event window, we find that public target shareholders receive a 63% (14%) higher premium when the acquirer is a public firm rather than a private equity firm (private operating firm). The premium difference holds with the usual controls for deal and target characteristics, and it is highest (lowest) when acquisitions by private bidders are compared to acquisitions by public companies with low (high) managerial ownership. Further, the premium paid by public bidders (not private bidders) increases with target managerial and institutional ownership.